Coordination to Reduce Maternal and Infant Mortality in Tasikmalaya District - Jiwa Riwayanti; Heru Nurasa; Erlis Karnesih (Program Pascasarjana Universitas Negeri Makassar, 2020)
This research explains coordination to reduce maternal and infant mortality rates in Tasikmalaya District. The background of this study is the phenomenon of high maternal and infant mortality rates in West Java including in Tasikmalaya District. The method used in this research is descriptive with a qualitative approach carried out through interviews and observations of the parties involved in the expanding maternal and infant survival in Tasikmalaya District, reinforced by secondary data studies from the results of previous research, as well as data from related institutions. In order for the system in coordination to be effective it is necessary to improve in several aspects related to the system in coordination, in which there are three main dimensions in coordination, the dimensions of the mandate, systems and behaviors.